Effect of Situational Interactive Respiratory Training System on Patients with Respiratory Dysfunction after Stroke - TAN Lishuang; WANG Na; ZHAO Xiaoxue; DU Tianshu; ZHANG Yan (康复学报)
ObjectiveTo explore the effect of situational interactive respiratory training system on respiratory function, swallowing function and activities of daily living of patients with respiratory dysfunction after stroke.MethodsA total of 60 patients with respiratory dysfunction after stroke who were treated in the Rehabilitation Center of the Affiliated Hospital of Liaoning University of Traditional Chinese Medicine from September 2018 to September 2020, which were randomly divided to the the control group and the observation group, with 30 cases in each group. The control group received regular rehabilitation training (respiratory training, speech training, swallowing training), and the observation group received breathing training on the basis of the control group, and the abdominal breathing and lip contraction breathing training methods of the control group were adjusted to use the situational interactive respiratory training system for breathing training. Firstly, the forced vital capacity (FVC), forced expiratory volume in one second (FEV1), peak expiratory flow (PEF), maximum expiratory time, pulse oxygen saturation (SpO2) were evaluated by the system, so as to provide basis for the formulation of respiratory rehabilitation training plan. Then, the patient faced the screen and aligns his mouth with the pressure sensor of the training system to perform lip-respiratory breathing. According to the patient's interest, two or three games were selected for respiratory rehabilitation training, one time a day, 15 minutes a time, five days a week, continuous training for eight weeks. Before intervention, after intervention for four, eight weeks, FVC, FEV1, PEF, breathing duration, respiratory rate (RR), SpO2 and other indicators were used to evaluate the patient’s respiratory function; the Watian drinking water test and the standardized swallowing assessment (SSA) was used to evaluate the patient's swallowing function; the Barthel index was used to assess the patient's activities of daily living.ResultsCompared with before intervention, FVC, FEV1, PEF, breathing duration, and BI scores of the two groups after intervention for four, eight weeks were significantly improved, while the Watian drinking water test score and SSA score were significantly reduced, and the difference was statistically significant (P<0.05). Compared with after intervention for four weeks, the FVC, FEV1, PEF and BI scores of the two groups after intervention for eight weeks were significantly improved, and the Watian drinking water test score and SSA score were significantly reduced, and the difference was statistically significant (P<0.05). Compared with the control group at the same time, the FVC, FEV1, PEF, breathing duration, and BI scores of the observation group after intervention for four, eight weeks were significantly higher, while the Watian drinking water test score and SSA score were significantly lower, and the difference was statistically significant (P<0.05).ConclusionThe situational interactive respiratory training system can effectively improve patients' respiratory function, swallowing function and activities of daily living, and is worthy of clinical application.